2014
DOI: 10.3748/wjg.v20.i29.10038
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits cell viability and mTOR downstream signaling in gastroenteropancreatic and bronchopulmonary neuroendocrine tumor cells

Abstract: Aspirin demonstrates promising anticancer properties for NETs in vitro. Further preclinical and clinical studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Although strong expression of p21 in gastroenteropancreatic neuroendocrine neoplasms has been previously associated with poor outcome [6], in our study, positive p21 expression showed limited correlations, possibly due to this duality. In vitro, induction of p21 has been associated with aspirin-induced inhibition of neuroendocrine tumour cell viability [63], further emphasising the controversies in the interpretation of p21 presence. Regarding other endocrine neoplasms, no difference of p21 levels in thyroid follicular adenomas and carcinomas has been found [64].…”
Section: P21mentioning
confidence: 99%
“…Although strong expression of p21 in gastroenteropancreatic neuroendocrine neoplasms has been previously associated with poor outcome [6], in our study, positive p21 expression showed limited correlations, possibly due to this duality. In vitro, induction of p21 has been associated with aspirin-induced inhibition of neuroendocrine tumour cell viability [63], further emphasising the controversies in the interpretation of p21 presence. Regarding other endocrine neoplasms, no difference of p21 levels in thyroid follicular adenomas and carcinomas has been found [64].…”
Section: P21mentioning
confidence: 99%
“…All human neuroendocrine cell lines were received and cultured as recently described [22]. The human pancreatic neuroendocrine tumor cell line BON1 [23,24] (kindly provided by Prof. R. Göke, Marburg, Germany) was grown in DMEM/F12 (1:1) supplemented with 10% FBS, 1% penicillin/streptomycin and 0.4% amphotericin B.…”
Section: Methodsmentioning
confidence: 99%
“…The GOT1 culture medium was additionally supplemented with 5 μg/mL apo-transferrin and 0.135 IU/mL insulin. All human neuroendocrine cell lines were received and cultured as described previously [16,17] . The cells were tested and determined to be mycoplasma free and incubated at 37 ° C and 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%